Religiousness/Spirituality in Oncological Patientes:: Life Quality and Health - Fornazari, Silvia Aparecida (2010)
The study investigated the religious coping in 10 cancer patients of a specialized institution, aged between 25 and 55 years old. The data were collected through interviews. The results were analyzed considering the content of the patients’ verbal report, described as: (1) categories of verbal report’s content (emotional support, healing, searching of meaning, contributions for treatment, and control); and (2) characteristics of religiousness/spirituality. All participants presented verbal reports with contents of religiousness/spirituality, which suggests that due to the relation between the disease and the possibility of death, religious coping became a strategy of stress reduction and quality of life improvement for those patients.